A comprehensive study of an atmospheric water generator using Peltier effect. (June 2018) - Shourideh, Amir Hossein; Bou Ajram, Wael; Al Lami, Jalal; Haggag, Salem; Mansouri, Abraham
Highlights: An atmospheric water generator that employs the Peltier effect was designed. The COP and water yield of the system were used as the main design criteria. An employed wet fin model, used for the fin design, was validated experimentally. The effects of varying air velocity, relative humidity, and current were tested. The prototype was compared to other thermoelectric prototypes in literature. Abstract: A prototype of a small-scale atmospheric water generator (AWG) that employs the Peltier effect for cooling was designed and constructed. In this study, a systematic design approach was employed, and the AWG system was sized using the cooling capacity and coefficient of performance (COP) behaviors of the thermoelectric cooler (TEC) with respect to the current. Likewise, a mathematical model that uses the surrounding fluid temperature and relative humidity ratio as the driving force for heat and mass transfer was used to optimize and design the rectangular extended surfaces and estimate the water generation rates. The completed AWG system, housed in a 3D printed casing, was used to experimentally investigate the impact of the variation of the airflow velocity, humidity, and TEC current on the water generation rates. The experiments confirm that the inclusion of an intake fan reduces water generation in some cases. The water yield is observed to increase with relative humidity. The tests also suggest that increasing the current of the individual TECs results in an increased water generation rate; however, this increase is coupled with a higher specific energy consumption as a result of the decreased COP. Finally, a comparison between the prototype and several AWGs in literature was carried out.